STRATEGI PENGINJILAN PAULUS DI FILIPI DALAM KITAB KISAH PARA RASUL 16:13-40 RELEVANSINYA BAGI PELAKSANAAN MISI MASA KINI - Johanes Witoro (STT BIBLIKA JAKARTA, 2021)
Evangelism is not just the job of a servant of God or a particular church organization, but the job of all believers. The purpose of this study is to explore the evangelistic strategies that the Apostle Paul used in the city of Philippi and presented descriptively. This research was conducted using a qualitative method with a study of the literature (library). First, an inductive excavation of the Bible about the efforts and ways of evangelizing the Apostle Paul was carried out, then the search for other sources that supported it. In the discussion it was found that the Apostle Paul's evangelism strategy in Philippi used a certain closeness method and a personal approach. It is concluded that the evangelism strategy used by the Apostle Paul is still relevant to the implementation of today's missions.